Vaccine effectiveness against influenza A in older adults and the effect of chronic conditions: results from the I-MOVE and VEBIS multicentre European hospital case-control studies, 2015/16-2023/24 - Rose, Angela Mary Catherine; Nicolay, Nathalie; Mazagatos, Clara; Martínez-Baz, Iván; Launay, Odile; De Mot, Laurane; Bella, Antonino; Lazar, Mihaela; Machado, Ausenda; Kuliešė, Monika; Abela, Stephen; Vučina, Vesna Višekruna; et al. (BMC medicine, 2025)
BACKGROUND: The Influenza - Monitoring Vaccine Effectiveness in Europe (I-MOVE/I-MOVE+) and Vaccine Effectiveness, Burden and Impact Studies (VEBIS) hospital networks have conducted seasonal multicentre, test-negative, case-control studies in Europe to measure influenza vaccine effectiveness (IVE) since 2015/16. We measured the effect of chronic conditions on VE of influenza A subtypes among older adults (≥ 65 years) using pooled-season data (2015/16-2023/24). METHODS: Hospital teams swabbed patients with severe acute respiratory infection (SARI) within 7 days of symptom onset. Cases were RT-PCR positive for influenza A(H1N1)pdm09 or A(H3N2); controls negative for any influenza virus. We calculated overall pooled-season IVE against influenza A(H1N1)pdm09 and A(H3N2), adjusted for study site, sex, age and onset date; and stratified by number of and by each chronic condition (diabetes, heart disease, lung disease/asthma, immunosuppression, kidney disease, liver disease, cancer, obesity). We investigated interaction between vaccination and each condition. RESULTS: We included 1805 A(H1N1)pdm09 cases with 16,329 controls; 2590 A(H3N2) cases with 14,920 controls, from 13 study sites (12 countries). Over all seasons, 63-67% cases and 70% controls had ≥ 2 chronic conditions. Against A(H1N1)pdm09, pooled-season IVE was 37% (95%CI: 29-44) overall; 49% (95%CI: 9-72), 30% (95%CI: 12-44) and 38% (95%CI: 29-46) in those with 0, 1, ≥ 2 chronic conditions. Most IVE point estimates were 34-45%, apart from immunosuppression (-7%), kidney disease (17%) and liver disease (54%), but 95% CIs overlapped. Significant interaction was observed for kidney disease (p = 0.02) and immunosuppression (p = 0.01). Against A(H3N2), pooled-season IVE was 17% (95%CI: 8-25) overall; 15% (95%CI: -26-42), 11% (95%CI: -8-27) and 18% (95%CI: 7-28) in those with 0, 1, ≥ 2 chronic conditions. Here, IVE point estimates ranged 13-25%, apart from immunosuppression (5%), kidney disease (6%) and liver disease (31%), although 95% CIs overlapped. There were no significant interactions. CONCLUSIONS: Pooled-season results suggest low-moderate VE against influenza A subtypes among older SARI patients; higher against A(H1N1)pdm09 than A(H3N2), with little evidence of chronic condition modifying effect, apart from kidney disease and immunosuppression. We stress the importance of developing improved influenza vaccines for specific populations, and encourage further research into the effect of chronic conditions on IVE in older adults.
Keywords: Influenza, Human; chřipka lidská; chronická nemoc; ženské pohlaví; lidé; Vaccine effectiveness; Influenza A Virus, H1N1 Subtype; virus chřipky A, podtyp H3N2; Aged, 80 and over; senioři; studie případů a kontrol; Aged; Influenza A Virus, H3N2 Subtype; Influenza Vaccines; Chronic Disease; Vaccine Efficacy; senioři nad 80 let; Humans; Influenza; virus chřipky A, podtyp H1N1; Case-Control Studies; Europe; mužské pohlaví; Hospital; Male; účinnost vakcíny; Evropa; Chronic conditions; vakcíny proti chřipce; Female